Comparative study of Spanish and Italian terrestrial small mammal coenoses from different biotopes in Mediterranean peninsular tip regions - Cagnin, M; Moreno, S; Aloise, G; Garofalo, G; Villafuerte, R; Gaona, P; Cristaldi, M (Journal of Biogeography, 1998)
A comparison of terrestrial small mammal coenoses belonging to nine different biotopes in the tips of the Iberian and Italian peninsulas was carried out using the pitfall trapping method. The influence of both habitat type and peninsular effect on composition of small mammal coenoses was analysed. In Southern Italy, 203 specimens belonging to seven species were trapped: Suncus etruscus (Savi, 1822), Crocidura suaveolens (Pallas, 1811), C. leucodon (Hermann, 1780), Microtus savii (de Sélys-Longchamps, 1838), Apodemus sylvaticus (L., 1758), A. flavicollis (Melchior, 1834) and Mus musculus domesticus Schwarz & Schwarz, 1943. In Southern Spain 428 specimens belonging to five species were trapped: Suncus etruscus, Crocidura russula (Hermann, 1780), Microtus duodecimcostatus (de Sélys-Longchamps, 1839), Apodemus sylvaticus and Mus spretus Lataste, 1883. The relative density of small mammals occurring in the nine Spanish sampling stations was twice that recorded in the Italian stations; however the number of species recorded in the different biotopes show similar mean values, ranging from three to five in Andalusia and from three to six in Calabria. Apodemus sylvaticus was the dominant species in the Calabrian stations, whereas Crocidura russula prevailed in Andalusia. The biotic diversity values are very similar in the Calabrian and Andalusian biotopes. By contrast, the Insectivora/Rodentia ratio was always higher in Andalusia. The more xerophytic biotopes showed greater similarities between the communities in Southern Spain and Southern Italy, while the cooler biotopes differed between these two peninsulas.
Keywords: habitat type; Italy; peninsular effect; sclerophyll biome; Small mammal communities; Spain